The "Care" learning model: The value education for strengthening the religious moderation - PF, Kadek Aria Prima Dewi; Perbowosari, Heny; Wahyuni, Ni Nyoman Tri (Edelweiss Applied Science and Technology, 2025)
This research discusses the importance of religious moderation in the context of diversity in Indonesia. The Republic of Indonesia, having over 17,000 islands and hundreds of ethnic groups, faces challenges related to diversity, particularly in terms of religion. The Indonesian government has developed a Religious Moderation Program as a strategy for preventing conflict. A "CARE" (Case Analysis, Resolution, and Engagement) learning method has been developed to address this challenge through value education, focusing on religious moderation. This model emphasizes training in critical thinking regarding the religious moral phenomena occurring in society. This research utilized an ADDIE (Analysis, Design, Development, Implementation, and Evaluation) improvement method to measure the effectiveness of the "CARE" learning model in improving students' understanding of religious moderation, tolerance, and intercultural cooperation.